11Effects of an Online Adventure Game on Vocabulary Acquisition - Sulaiman, Sovan; Sadq, Kochar A.; Othman, Murad S. (Mitanni Journal of Humanitarian Sciences, 2022)
_ Online adventure game learning can motivate engaging and fun activities to learn new vocabulary. In the present study, the effect of using a digital online adventure game and its role in promoting Kurdish learners’ vocabulary learning and their level of motivation in playing the game were investigated. In the experimental group, the Hidden Chronicles online adventure game was used, whereas in the control group, English vocabulary was taught through traditional methods. At the end of the 3 weeks of traditional homework and gameplay, the participants’ performances were compared. The results pointed out that the mean score of the children in the experimental group was not significantly higher than those in the control group, meaning that there was no positive effect of using online adventure games in teaching English vocabulary to Kurdish learners. Regarding the pretest and posttest conditions in the experimental group, there was a significant difference in the scores for pretest and posttest conditions in the experimental group.